NOTES-Operationen in der Viszeralchirurgie: aktueller Stand = NOTES in visceral surgery : current status - Kähler, Georg (Der Chirurg, 2017)
The idea to use natural orifices as an access route for operations in the body has inspired many clinicians and researchers worldwide. Some of these expected a continuation of the development from open surgery to laparoscopic surgery finally to a less invasive modality. Others hoped for economic benefits for endoscopists to take over previous surgical patients into gastroenterological departments. The first experimental studies demonstrated that the initial expectations could not be implemented in a short period of time. The available endoscopes could not be proved for advanced procedures. Key problems like sterility, infection control, tissue manipulation, safety of access closure, and specimen retrieval manifested to be too large for routine clinical use. However, the attraction of the natural orifice transluminal endoscopic surgery (NOTES) philosophy has resulted in a reduction of the number and diameters of trocars in laparoscopic surgery. Hybrid NOTES as a combination of classical laparoscopic access with natural orifice instrumentations (mostly transvaginal) have become clinical reality in many hospitals. This development fits into the long-term trend towards less invasive surgery and more effective interventional methods in endolumenal endoscopy.